Pet Store Loyalty in Malaysia - Leong, Yuen Yee (2010)
Loyalty is open studied topic within the retailing and marketing discipline. A strong and profitable base of loyal customers is an asset to any organization, and is one of the epitomes of success for a company. The flourishing of large, specialty niche retailers like Starbucks, Victoria Secret and Barnes & Noble are stellar success stories that thrive on their troop of staunch followers. Pet retailing is a niche market which has its own interesting market characteristics. The emergence of the pet superstores in the 1990s, the like of PetSmart in the US, with 1,160 stores in the US and Canada, as well as Pets At Home in the UK with 266 stores to date, changes the competitive landscape for the traditional pet retailers. In Malaysia, a similar trend started a decade or so ago, with the influx of homegrown and regional large pet retail chain stores This study aims to explore the antecedents of loyalty, benefits of loyalty and the types of loyalty that exist among the pet owners towards the special pet retail stores in Malaysia. The research is conducted via one-to-one interviews with a group of 19 pet owners. The findings of the five key factors that engender loyalty and the three core types of loyalty benefits are compatible with previous studies on the frameworks and models for store loyalty, the antecedents of loyalty and its benefits. The results from this study are useful to current and emerging pet retailers in Malaysia to understand and leverage on the key drivers of loyalty, and the benefits valued by their customers/pet owners. This, in turn, leads to growth in their businesses, and increase in profitability. Such knowledge and insights into the loyalty factors valued by the customers create a competitive edge for pet retailers to succeed in a highly competitive, maturing and low -differentiation buyer's market.